ANALISA FASIES DAN STUDI PALEOGEOGRAFI FORMASI NGRAYONG LAPANGAN „STARK‟ CEKUNGAN JAWA TIMUR UTARA MENGGUNAKAN SIKUEN STRATIGRAFI BERDASARKANDATA WIRELINE LOG, CUTTING, SWC, BIOSTRATIGRAFI DAN PETROGRAFI - Muhammad Rabbani (Jurnal Ilmiah Geologi PANGEA, 2016)
ABSTRACT - The researches area are located in one of the PT. Pertamina exploration field in North East JavaBasin. Fields "STARK" included in the North East Java Basin, Central Java, where the focus of the research wasthe determination of facies and depositional environment Ngrayong Formation. The study was conducted usingdata owned by PT. Pertamina EP., Including seismic and well log data as the main data and Sidewall Core data,mud log, petrographic section, and biostratigraphy as additional data. The well data that we used for this researchis well M-001 445-771 TVD, well M-002 860-1253 TVD and well M-003 1584 – 1835 TVD. Stratigraphicfeatures of this researches are the top Ngrayong Formation above by an unconformity underlying the BuluFormation and the bottom of Ngrayong Formation unconformably the Tawun Formation. The geologicalstructure is evolving STARK Field anticline and inversion fault. Based on data biostratigraphic age NgrayongFormations are N9-N13. Lithology in Ngrayong Fromation comprises predominantly by clastic limestonewackestone - packestone, shale, calcareous sandstone, and siltstone. Facies and depositional environment thatdeveloped in Ngrayong Formation, Fields "STARK" consists of carbonate mixture of sediments onshore or mixcarbonate terrigenous shorline facies whcih is Skeletal Limestone, laminated limestone and interlaminatedlimestone facies and the paleoenvironment that develops is lagoon, tidal flats, tidal channels, offshore bars.Ngrayong Formation through 3 sequences phases. The first sequence developed LST 1, TST 1 and HST 1.Second, developing TST 2 and HST 2. And final phase LST3, TST3 and HST 3. Keywords : sequence stratigraphy, wireline log, biostratigraphy, Ngrayong Formation